URASP: an ultralightweight RFID authentication scheme using permutation operation - Mohd Shariq; Singh, Karan; Maurya, Pramod Kumar; Ahmadian, Ali; Kamel Ariffin, Muhammad Rezal (Springer, 2021)
Due to low-cost, ease of use and convenience, Radio Frequency IDentification (RFID) is a contactless technology that has become more and more promising for automatic identification of an object and people without physical contact. However, the RFID system faces major issues related to its security and privacy, where an adversary may eavesdrop, temper, modify, and intercept the transmitted messages over a communication channel. To overcome these issues, there is a flexible and effective way to implement an ultralightweight RFID scheme. Therefore, we present an ultralightweight RFID authentication scheme using permutation operation named URASP in this paper. Our proposed scheme integrates permutation and left rotate operation to provide a higher level of security and privacy without increasing storage and computation overhead. In addition, the informal analysis of our proposal illustrates its ability to overcome all known security attacks. We show that the proposed URASP scheme preserves the properties of tags untraceability and information privacy by using Juels and Weis privacy model. The performance analysis has been performed which demonstrates that the proposed scheme outperforms other existing schemes as well as utilizes fewer resources on tags. The verification of our scheme has been done using Scyther simulation tool. Thereafter, the correctness of our scheme has been verified by using BAN logic inference rules. Hence, the proposed scheme is more suited for low-cost passive RFID tags.